John Harbison’s Use of Music of the Past in Three Selected Compositions - Peter Silberman (Gamut: Online Journal of the Music Theory Society of the Mid-Atlantic, 2013)
John Harbison’s music is rich in allusions to music of the past. Many of his compositions incorporate excerpts from pre-existing works or newly written passages in earlier styles, predominantly jazz. This article discusses the interaction of pre-existing and new music in three compositions by Harbison (Twilight Music, the Gatsby Etudes, and November 19, 1828), as well as three modes of borrowing used by Harbison (misreading, pastiche, and quotation). Each analysis examines how Harbison transforms pre-existing tonal material to create a post-tonal work, and shows that Harbison’s integration of tonal and post-tonal materials varies depending on the mode of borrowing.